The Applicability of Artificial Intelligence to the Health-care Sector - Bhosale, Shamal P. (Asian Journal of Pharmaceutics (AJP), 2024)
Almost all sectors are seeing an increase in the use of artificial intelligence (AI). It can be applied in a variety of sectors, including research, technology, and health, and is not limited to any one area. Artificial intelligence (AI) focuses mostly on how computers simulate human brain processes through data analysis. AI can be a potential option to solve all the drawbacks of medication development, which include expensive research and development expenses and unknown time consumption. There is a possibility of overlooking some important information because so much data are available. Expert systems, deep learning, and machine learning algorithms are some of the methods being used to overcome these problems. Drug development delays and clinical and commercial failures can be minimized with the effective application of AI in the pharmaceutical industry. This evaluation includes details on AI’s evolution, subfields, general implementation, and use in the pharmaceutical industry. It also offers insights into AI’s shortcomings and obstacles.